Gamification and Animation in E-Learning: A Case Study on Engagement and Perceived Effectiveness Among Animation Students - Ahmad, Muhammad Fazrulhelmi; Mohd Dzulkifli, Dzunnur Zaily; Mohd Zainuddin, Mohamad Ridhwan; Md Hani, Mohd Hatta; Afandi, Mohamad Fazirul Rafiq (JBS Nexus, 2025)
Despite growing interest in using gamification and animation to enhance online education, limited research addresses how effectively these methods improve student engagement, motivation, and perceived effectiveness in specialized disciplines such as animation technology. This study investigates the role of gamification and animation in enhancing student engagement, motivation, and perceived effectiveness within an e-learning environment. Using a descriptive survey method, data were collected from 86 Diploma in Animation Technology students through structured questionnaires that measured their perceptions and experiences. The findings revealed strong positive perceptions toward animated and gamified content, with students agreeing that these methods significantly improved their understanding, academic performance, critical thinking, and knowledge retention. Furthermore, correlation analysis showed a strong positive relationship (r = 0.892) between student engagement and perceived effectiveness of gamification and animation. Thus, this research confirms that strategically integrating gamification and animation in e-learning can substantially enhance student engagement, learning effectiveness, and overall educational experiences.